Cardiac Surveillance for Early Detection of Late Subclinical Cardiac Dysfunction in Childhood Cancer Survivors After Anthracycline Therapy - Sofia, Rosaria; Melita, Veronica; De Vita, Antonio; Ruggiero, Antonio; Romano, Alberto; Attinà, Giorgio; Birritella, Lisa; Lamendola, Priscilla; Lombardo, Antonella; Lanza, Gaetano Antonio; Delogu, Angelica Bibiana (Frontiers in Oncology, 2021)
Background In childhood cancer survivors (CCSs) anthracycline-related cardiotoxicity is an important cause of morbidity and late mortality, but the optimal modality of cardiac surveillance still remains to be defined. The aim of this study was to assess whether non-invasive echocardiography-based functional cardiac measures can detect early subclinical myocardial changes in long-term pediatric cancer survivors who received anthracycline therapy. Methods Twenty anthracycline-treated long-term CCSs and 20 age, sex, and body surface area matched healthy controls were enrolled in this study. Among cancer survivors, mean age at diagnosis was 6.5 ± 4.4 years, and the mean cumulative anthracycline dose was 234.5 ± 87.4 mg/m2. All subjects underwent a comprehensive functional echocardiographic protocol study including two-dimensional echocardiography (2D Echo), tissue Doppler imaging (TDI), speckle tracking (STE) and three-dimensional echocardiography (3D Echo). Patients were studied at a mean follow-up time of 6.5 ± 2.8 years from the end of therapy. Results No significant differences in two-dimensional left ventricle ejection fraction (LVEF), diastolic parameters and speckle tracking (STE)-derived myocardial strain were observed between patients treated with anthracyclines and controls. Myocardial performance index was significantly prolonged (p = 0.005) and three-dimensional LVEF was significantly reduced (p = 0.002) in CCSs compared to controls, even though most values were within the normal range. There were no significant correlations between 2D, STE, and 3D echocardiographic parameters and age at diagnosis or duration of follow-up. No significant differences in echocardiographic parameters were found when stratifying cancer patients according to established risk factors for anthracycline cardiomyopathy. Conclusions This study found significantly reduced three-dimensional LVEF in CCSs compared with controls, despite no significant differences in two-dimensional LVEF and longitudinal strain values. These findings suggest that long-term CCSs who had received anthracycline therapy may be found to have subclinical features of myocardial dysfunction. However, further studies are needed to demonstrate the validity of new imaging techniques, including STE and 3D Echo, to identify patients at risk for cardiomyopathy in the long-term follow-up of CCSs.